Palladium‐Catalyzed C‐N Bond Formation: A Straightforward Alkoxymethylation Process for the Synthesis of the C1 and C3‐Dialkoxy Indoles. Issue 48 (21st December 2020) - He, Jiaming; Yu, Yue; Guo, Pengfeng; Liu, Xiang; Zhu, Baofu; Cao, Hua
Abstract: A novel approach for the synthesis of the C1 and C3‐dialkoxy indoles has been developed for using 2‐(phenylethynyl)aniline with formaldehyde and alcohols under the catalysis of acid and palladium acetate. This multicomponent reaction that provides a straightforward alkoxymethylation process to construct substituted indoles is expected to be an important method for the synthesis of indole derivatives. Abstract : Indole was widely found in natural products and functional materials that exhibit important biological activities and broad applications in drugs and organic material. A novel and efficient strategy for the synthesis of 1, 3‐disubstituted alkoxy indole derivatives by Palladium‐catalyzed the reaction of 2‐(phenylethynyl)aniline, formaldehyde, and alcohol.